TO STUDY THE EFFICACY OF AGNIKARMA IN VATAKANTAKA W.S.R.TO PLANTER FASCIITIS - V Shekokar, Anantkumar; M Borkar, Kanchan; Patle, *Rajani (AYUSHDHARA, 2017)
Heel pain symptom is commonly found in 80% of population in the society. Vatakantaka is the painful condition in which the person can’t walk properly, that hampers his daily activity. Almost all signs and symptoms of Vatakantaka resembles with the condition of chronic plantar fasciitis described by the modern texts. Chronic plantar fasciitis is mostly required analgesic and anti-inflammatory and surgical correction to stabilize the patient as well as to cure the condition, but in developing countries such type of treatment modalities were avoided because of Complications of NSAID, pain, fear and other psychological factors, longer hospitalization and also economical expenses. So there is scope for non surgical treatment modalities with less economical expenditure as well as minimum hospitalization. Agnikarma has Shulahara, Shothahara and Vatahara properties, less painful with minimum expenditure. Hence it can be proved as a most affordable and convenient parasurgical treatment modalities in the developing countries which can provide relevant treatment modalities in medical sciences. In the present study in dependable variables are Agnikarma and Inj. Therapy while dependable variables are Vedana, Stambha, Sparashasahatva, Kriyahani and demographic variables are age, sex, religion, habitat, Prakruti, diet etc. The present study designed as a prospective randomized control single blind clinical trial with hypothesis that, Agnikarna acts as Shulahara, Shothahara and Parasurgical properties in management of Vatakantak. In the present study, 60 patients of Vatakantak will be selected & randomly categorized in to 2 groups, each of comprising 30 Patients. and following hypothesis should be considered. Agnikarma acts as a Shulahara, Shothahara and Parasurgical properties in management of Vatakantak. Result of present study shows significant result in Vatakantak to cure as well as prevent recurrences of the condition.